Dynamics of Neural Adjustments During Progressive Transitions to Unweighted and Reloaded Running - Camille Fazzari; Robin Macchi; Rémy Casanova; Pascale Chavet; Jacques Duchateau; Caroline Nicol (Scandinavian Journal of Medicine & Science in Sports, 2026)
ABSTRACT The lower body positive pressure treadmill (LBPPT) enables running at different percentages of body weight. This study investigated how neural adjustments unfold during progressive transitions to unweighted and reloaded running, and assessed the repeatability of their dynamics across two successive exposures. Thirty‐eight men completed two runs (RUN1, RUN2) on a LBPPT. Each run comprised three stable phases at 100%, 60%, and 100% body weight (3 × 3 min), separated by progressive unweighting and reloading transitions (UNW tr and RLD tr ; 12 ± 2 s). Surface electromyographic (EMG) activity of 11 lower limb muscles was recorded. Root mean square EMG and muscle synergies were analyzed for each running cycle separately. In RUN1, some adjustments—including those in hamstring preactivation, as well as in triceps surae braking and push‐off activity—remained incomplete at the end of UNW tr . Moreover, a stabilizing muscle synergy was transiently recruited. In RUN2, however, these adjustments occurred more rapidly. In both runs, all neural adjustments were completed at the end of RLD tr . During UNW tr , runners encountered a novel sensorimotor context, where the gradual decrease in mechanical constraints interacted with the gradual increase in sensory and temporal constraints. Such context challenged the nervous system in RUN1, but was integrated more rapidly in RUN2, providing strong evidence of savings. In contrast, RLD tr reinstated a familiar sensorimotor context, allowing for complete neural adjustments in both runs. These results highlight the relevance of unweighing and reloading transitions for evaluating and rehabilitating locomotor adaptability in clinical and athletic settings.